Compassionate capitalism : business and community in medieval England - Casson, Catherine; Casson, Mark, 1945-; Lee, John S.; Phillips, Katie (Bristol : Bristol University Press, 2020)
It may seem like a recent trend, but businesses have been practising compassionate capitalism for nearly a thousand years. Based on the newly discovered historical documents on Cambridge's sophisticated urban property market during the Commercial Revolution in the thirteenth century, this book explores how successful entrepreneurs employed the wealth they had accumulated to the benefit of the community. Cutting across disciplines, from economic and business history to entrepreneurship, philanthropy and medieval studies, this outstanding volume presents an invaluable contribution to our knowledge of the early phases of capitalism. A companion book, The Cambridge Hundred Rolls Sources Volume, replacing the previous incomplete and inaccurate transcription by the Record Commission of 1818, is also now available from Bristol University Press.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Land use -- England -- Cambridge; Industries -- Social aspects -- England -- Cambridge; Social responsibility of business -- England -- Cambridge; Social entrepreneurship -- England -- Cambridge; Cambridge (England) -- Economic conditions